An empirical study of input methods deployed during treatment session in a clinical system / Fakhrul Hazman Yusoff, Norlis Othman and Abidah Hj. Mat Taib - Yusoff, Fakhrul Hazman; Othman, Norlis; Mat Taib, Abidah (Universiti Teknologi MARA, Perlis, 2003)
This paper study the effect of using various input methods such as keyboard, Personal Digital Assistant and touchscreen to input patient information during patient-doctor treatment or consultation session. This input interface integrates into a clinical information system that consists of modules such as patient registration, databases and prescription management. The system will accumulate patients' data and produce reports as required by any of the user in the network. It will assimilate the conventional method used by the users, in this case, doctors for data entry and menu navigation into the project. This will make the clinic daily operation more efficient and automatically increase the productivity in the workplace. This can be gain through lessening the time for patient registration and the waiting time between patients. Theoretically it will also reduce the patient-doctor consultation time. Hence, a viable solution is identified for a user friendly, ergonomic input device to reduce the psychological barrier between patients and doctors that exists while the doctor is keying the patient's diagnosis during consultation and also the phobia that users usually develop in the computerization stage.